Efficacy of intra-operative adductor canal block in total knee arthroplasty: a prospective observational study - V., Karthik; S., Rajavarman; Janghid, Subhash (International Journal of Research in Orthopaedics, 2026)
Background: Effective postoperative pain control after total knee arthroplasty (TKA) remains a clinical challenge. This study aimed to evaluate the efficacy of intraoperative adductor canal block (ACB) in providing pain relief and preserving quadriceps function. Methods: This prospective observational study included 92 patients undergoing primary TKA. Intraoperative ACB was administered by the operative surgeon, and outcomes assessed included pain scores (visual analogue score (VAS) at multiple time points), quadriceps muscle power, complications, and postoperative analgesic use. Statistical associations were evaluated using Chi-square and t-tests with p<0.05 as significant. Results: Most participants reported mild pain at 6–8 hours, with moderate pain predominating at 24–48 hours and during mobilization. Quadriceps strength was preserved in nearly half the patients. Analgesic consumption correlated with higher VAS at 48 hours (p=0.001). Age was associated with reduced quadriceps strength (p=0.011). Longer preoperative pain duration was significantly linked to higher postoperative pain at 24–48 hours. Conclusions: Intraoperative Adductor canal block is an effective, motor-sparing analgesic option for TKA, supporting early mobilization and reducing dependence on opioids. Further research is warranted to optimize block techniques and adjunct strategies.